Nitrogen concentration acting as an environmental signal regulates cyanobacterial EPS excretion. (March 2022) - Qian, Long; Ye, Xingwang; Xiao, Jingshang; Lin, Simeng; Wang, Hongyu; Liu, Zhe; Ma, Yongfei; Yang, Lie; Zhang, Zulin; Wu, Li
Abstract: As an important carbon (C) storage in biological soil crusts (BSCs), exopolysaccharides (EPSs) are not only a part of the desert C cycle, but also the key materials for cyanobacteria to resist desert stress. In this study, the influence of initial N concentrations (10, 25 and 50 mg L −1 designated as N10, N25 and N50 respectively) on Microcoleus vaginatusis growth and the excretion of EPSs including RPS (released exopolysaccharides) and CPS (capsule exopolysaccharides) were evaluated at different growth periods. In logarithmic period, higher ratio of biomass to EPSs indicated by (DW-CPS)/EPSs was observed in the N50 group with the highest N concentration (about 40 mg L −1 ) in the medium, while no difference was observed among the three groups in stationary period when the N concentrations of medium were lower than 25 mg L −1 . The CPS/RPS showed similar results with (DW-CPS)/EPSs, and stayed higher than 1 in each group. Notably, obvious difference displayed in the monosaccharidic composition and morphologies between CPS and RPS, but not the N levels. The changes of C/N in cells at different growth period indicate that the excretion of EPSs, a mechanism that maintains the balance of cell C/N ratio, only works when the N in the environment is sufficient. Our results showed that, as the raw material and environmental signal, environmental N concentration regulates the elements (C and N) percentage of cyanobacterial cells and its EPSs excretion pattern, but not the monosaccharidic composition or the morphologies. These results also implied that, as the essential self-protecting materials, more EPSs with higher proportion of CPS would be excreted to response the low N environment. Graphical abstract: Image 1 Highlights: N regulates the C/N of cyanobacterial cells and EPS excretion pattern. More EPS with higher portion of CPS was excreted under low N level. N level had no effect on the monosaccharidic composition and morphology of EPS. Significant difference in monosaccharidic composition and morphology was found between RPS and CPS.